Advancement of a High-Efficiency Wearable Antenna Enabling Wireless Body Area Networks - Mohamed Ibrahim Waly; Amor Smida; Nasser Ali Aljarallah; Ridha Ghayoula; Ahmed S. Negm; Surajo Muhammad; Jun Jiat Tiang; Amjad Iqbal (IEEE Access, 2023)
This paper presents a unique antenna that is designed to be efficient, with improved gain and partial flexibility, for use in wearable biomedical telemetry applications. The antenna design utilizes a semi-flexible RO5880 substrate material (dielectric constant, $ε _{r}$ = 2.2, loss tangent, ( $\tan δ $ ) = 0.0009) with physical dimensions measuring 0.47 $λ _{g} × $ 0.47 $λ _{g}$ . The model involves the incorporation of rectangular inverted “C” slots, which effectively results in a reduction of the resonant frequency. Additionally, a distributed rectangular slot is introduced on the ground plane, contributing to the augmentation of the operational bandwidth. The operational frequency of the proposed antenna design is 2.40 GHz, accompanied by a bandwidth (BW) of 320 MHz at a −10 dB level. This equates to a fractional percentage bandwidth (FBW) of 13.33% centered around the frequency of 2.40 GHz. The antenna design presented in this work demonstrates the preservation of improved gain and efficiency, achieving values of 3.67 dBi and 94%, respectively, at a frequency of 2.40 GHz. The work demonstrates through simulation and experimental outcomes that the antenna exhibits minimal impact on parameters such as gain reflection coefficient $(|S_{11}|)$ , BW, and bending efficiency. Furthermore, the antenna underwent simulation and experimental testing in close proximity to the human body, revealing favorable operational characteristics. The proposed antenna exhibits substantial potential as a viable option for wearable biomedical instruments. Thus, the proposed wearable antenna design in this study offers a wideband antenna for ISM band applications, expanding bandwidth without compromising performance. Bending the antenna minimally affects gain, bandwidth, and efficiency when worn on the body, making it suitable for wearables. It also maintains a reasonably low Specific Absorption Rate (SAR), reducing wave absorption by the body. Unique features like rectangular inverted “C” slots and a distributed rectangular slot on the ground plane enhance bandwidth while maintaining performance during bending.